Endodontic therapy of a mandibular premolar with three root canals: Two case reports - Ilić Jugoslav; Vujašković Mirjana; Nedeljković Ružica (Serbian Medical Society - Dental Section, Belgrade, 2010)
The most important requirements for successful endodontic treatment are accurate diagnosis and good knowledge of canal morphology. A mandibular second premolars rarely have more than one root and one root canal. Data from the literature indicate low percentage of a mandibular premolars with three or more root canals. Unusual morphology of the root canal system is diagnostic and therapeutic challenge. It is very important to analyze preoperative radiograph and to explore thoroughly the entrance of the root canal. The aim of this study was to present two patients who had lower second premolars with three canals that required endodontic therapy.